Is 46XX karyotype always a female?. (18th July 2012) - Ahmad, Ayesha; Siddiqui, Mohammad Asim; Goyal, Anju; Wangnoo, Subhash Kumar
Abstract : A19-year-old man, from a middle east country was referred by his physician to the endocrine department for bilateral gynaecomastia, low libido and sparse facial hair. There was no history of any chronic illness, mumps or traumatic injury to testis. He had clinical features suggestive of gonadotropin deficiency which was confirmed on biochemical testing. On karyotype and fluorescent in situ hybridisation analysis, he was found to have 46XX(SRY+) karyoptype.